Current Thoughts on Dementia From Risk Factors to Therapeutic Interventions - Ashraf, Ghulam Md.; Uddin, Md. Sahab (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This informative book discusses the latest research on the risk factors and therapeutics in dementia. WHO calls dementia a public health priority. Dementia manifests as a group of symptoms associated with decline in memory or other thinking skills and is severe enough to reduce a person's ability to perform everyday activities. It occurs frequently among elderly people, but it is not necessarily part of the normal aging process. The book has been divided into two broad sections. The first section reviews the risk factors involved in developing dementia, including various medical conditions, lifestyle choices, as well as genetics. The latter section describes various therapeutic interventions in dementia. Although there is no known cure for dementia, this book underlines the current treatment strategies that could momentarily reduce the symptoms and improve the quality of life of the patients. This book highlights the global effort to find better ways to halt the progression of dementia and develop novel therapeutic strategies. The book would be an interesting read for advanced graduate students and researchers working in the field of neuroscience, genetics, and medicine. It will generate good interest to neurologists, psychiatrists, geriatricians, cardiologists, internal medicine practitioners, epidemiologist, and public health workers.
Chapter 1. ApoE: A Risk Factor for Dementia -- Chapter 2. Infection-Induced Systemic Inflammation and Dementia -- Chapter 3. Role of Impaired Insulin Signaling in the Pathogenesis of Dementia -- Chapter 4. Sex Hormones as Risk Factors of Dementia -- Chapter 5. Mitophagy Impairments as Culprit of Alzheimer's Disease -- Chapter 6. Parkinson's Disease: Neurochemistry and Pharmacological Treatment -- Chapter 7. Emerging Roles of TREM2 in Neurodegenerative Diseases -- Chapter 8. Molecular Mechanisms Underlying the Role of HSPB8 in Neurodegeneration -- Chapter 9. Molecular Insights into the Role of ER Stress in Neurodegenerative Diseases. Chapter 10. Role of Hypertension and Hyperlipidemia in the Pathogenesis of Dementia -- Chapter 11. Behavioral Abnormalities of Gut Microbiota and Progression of Dementia -- Chapter 12. Gut-Brain Axis in Alzheimer's Disease: Interplay between Cholecystokinin, Dysbiosis, and Brain-Derived Neurotrophic Factor -- Chapter 13. Cholesterol and Dementia: A Possible Therapeutic Approach -- Chapter 14. Therapeutic Potential of PPARs in Alzheimer's Disease -- Chapter 15. Exploring the Role of Statins in Reversing the Cognitive and Neurovascular Dysfunctions in Dementia -- Chapter 16. Role of Immunotherapy in Ameliorating Proteopathic Dementia -- Chapter 17. Hypoxic-Hyperoxic Training in Dementia -- Chapter 18. Music Therapy in Dementia -- Chapter 19. Beneficial Effects of Citrus Flavonoids against Agb (BPathology in Alzheimer's Disease -- Chapter 20. Therapeutic Potential of Phytochemicals: Lessons Learned from Streptozotocin-Induced Sporadic Alzheimer's Disease -- Chapter 21. Concept of Amnesia and Dementia in Unani System of Medicine -- Chapter 22. Nanotechnological Applications in the Diagnosis and Treatment of Alzheimer's Dementia.s
Keywords: Neurosciences; Zoology; Medical genetics; Biotechnology; Medicine-Research.; Biology-Research.; Neuroscience; Zoology; Medical Genetics; Biotechnology; Biomedical Research